DIFFERENTIAL-ALGEBRAIC EQUATION FOR DECENTRALIZED SLIDING CONTROL METHOD - Maddileti, Dr. Kuruva (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
A Differential-Algebraic Equations (DAE) system is a system of equations that either contains differential equations and algebraic equations, or is equivalent to such a system. In mathematics these are examples of differential algebraic varieties and correspond to ideals in differential polynomial rings. It is used to control the method to simulate the system, while satisfying the algebraic constraints which is formulated. Because of the large amount of computation and communication associated with large scale matrix inversion problems in the existing centralized approaches, this new distributed method is much more efficient. Therefore, by using this novel method for distributed simulation of Differential Algebraic Equation systems is developed based on purely decentralized sliding mode is controlled for applying simulation of a multiple- pendulum system. Hence, this method performs better results interms of performance and stability.